Real-time search in the laboratory and the market - Meta Brown; Christopher J. Flinn; Andrew Schotter (Federal Reserve Bank of New York, 2009)
While widely accepted models of labor market search imply a constant reservation wage policy, the empirical evidence strongly suggests that reservation wages decline in the duration of search. This paper reports the results of the first real-time-search laboratory experiment. The controlled environment that subjects face is stationary, and the payoff-maximizing reservation wage is constant. Nevertheless, subjects' reservation wages decline sharply over time. We investigate two hypotheses to explain this decline: 1) searchers respond to the stock of accruing search costs, and 2) searchers experience nonstationary subjective costs of time spent searching. Our data support the latter hypothesis, and we substantiate this conclusion both experimentally and econometrically.
Keywords: C91; J64; 330; Job search; consumer search; reservation wage; experiment; Arbeitsplatzsuchmodell; Anspruchslohn; Test